A hepatic sparganosis misdiagnosed as intrahepatic mass-forming cholangiocarcinoma: a case report and literature review - Wang, Yinjiao; Lou, Yu; Chen, Lang; Yang, Xin; Cao, Aihong; Du, Peng (Frontiers in Oncology, 2024)
Hepatic sparganosis (HS) is extremely rare and has not been previously reported in Eastern China. We report the diagnosis and treatment of a patient with HS from Xuzhou City, Jiangsu Province, China. The patient was admitted due to an acute biliary tract infection, and the symptoms improved after treatment at the Gastroenterology Department. During an ultrasound examination on admission, an abnormal echo was incidentally discovered at the junction of the left and right lobes of the liver. Thereafter, upper abdominal computed tomography (CT) and magnetic resonance imaging (MRI) non-contrast and contrast-enhanced examinations, and serum tumor biomarker examination were completed. After a multidisciplinary treatment (MDT) discussion at the Department of Hepatobiliary Surgery, the patient was diagnosed with intrahepatic mass-type cholangiocarcinoma (IMCC) and surgery was recommended. The patient underwent surgical treatment, and postoperative pathology revealed HS. No signs of intrahepatic recurrence were observed during the 1-year follow-up period.